MEWUJUDKAN TARGET MDGS PENDIDIKAN UNTUK KEMAJUAN PENDIDIKAN MASA DATANG - Hudha, Atok Miftachul (Jurnal Bestari, 2009)
The Millennium Development Goals (MGDs) consist of quantitative objectives to be achieved within a certain period of time, especially the issue of poverty reduction by 2015. These were drawn from the Millennium Declaration and Indonesia was one of the 189 signatory countries in September 2000. Eight Millennium Development Goals also explains the objectives of human development, which can also directly impact the extreme poverty eradication. Each goal consist of the MDGs targets  that have a minimum limit of achievement that must be met by Indonesia in 2015. One of target goals is achieve universal primary education. In 2015, all Indonesian children both male and female will be able to complete their primary education. The Indonesian Government is committed to meet this target with the 9-year compulsory education program. This policy has been proved to improve access to primary education.